The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/fare.12002
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Gender Role Orientation and Dyadic Coping in Immigrant Latino Couples: Effects on Couple Functioning

Abstract: The main goal of this study was to examine from a systemic‐transactional stress perspective (Bodenmann, 1997) whether a more traditional gender role orientation may affect psychological aggression and relationship satisfaction directly and indirectly by decreasing supportive (partner's efforts to help the other partner cope with stress) and common dyadic coping (partners' conjoint efforts to cope with stress) among first‐generation immigrant Latino couples. Structural equation modeling results from 104 couples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 25 publications
6
48
1
1
Order By: Relevance
“…Though the authors did not test the three-way interaction tested in this study, this finding supports the notion that incongruence between husbands' attitudes and wives' behavior may be negatively related to husbands' marital satisfaction (Vannoy & Philliber, 1992). Although the empirical literature is limited, several scholars have argued for the theoretical importance of further examining the association between husbands' marital satisfaction and the interaction of spouses' gender role attitudes and wives' employment status both among White couples (Vannoy & Philliber, 1992) and Latino couples (Falconier, 2013;Updegraff et al, 2007).…”
Section: Status and Husbands' Marital Satisfactionsupporting
confidence: 59%
See 4 more Smart Citations
“…Though the authors did not test the three-way interaction tested in this study, this finding supports the notion that incongruence between husbands' attitudes and wives' behavior may be negatively related to husbands' marital satisfaction (Vannoy & Philliber, 1992). Although the empirical literature is limited, several scholars have argued for the theoretical importance of further examining the association between husbands' marital satisfaction and the interaction of spouses' gender role attitudes and wives' employment status both among White couples (Vannoy & Philliber, 1992) and Latino couples (Falconier, 2013;Updegraff et al, 2007).…”
Section: Status and Husbands' Marital Satisfactionsupporting
confidence: 59%
“…Similarly, Peplau (1983) suggested that the interaction of spouses' attitudes is likely a stronger predictor of husbands' marital satisfaction than wives' marital satisfaction. Falconier (2013) found that the extent to which (a) men held more sex-typed attitudes and (b) that there was discrepancy between husbands' own gender role attitudes and the attitudes of their wives predicted Mexicanorigin husbands' marital satisfaction. Among more sex-typed husbands, when attitudinal ideals cannot be enacted and men consider their provider "territory" to be threatened by their wives' employment, it follows that men who hold more sex-typed attitudes would be less satisfied in their marriages.…”
Section: Husbands' and Wives' Gender Role Attitudes And Husbands' Marmentioning
confidence: 95%
See 3 more Smart Citations